2017
DOI: 10.4078/jrd.2017.24.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Circulating Adiponectin, Visfatin, and Ghrelin Levels in Patients with Systemic Lupus Erythematosus

Abstract: Objective. To evaluate the association between circulating adiponectin, visfatin, and ghrelin levels and systemic lupus erythematosus (SLE). Methods. We conducted a meta-analysis to compare serum/plasma adiponectin, visfatin, and ghrelin levels in patients with SLE to those of healthy controls. Results. Eleven articles (822 patients with SLE and 676 controls) were included in the meta-analysis. The meta-analysis showed that the adiponectin level was significantly higher in the SLE group than in the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Serum adiponectin was high in both SLE and RA patients in comparison to control (P <0.001). Many studies showed that adiponectin was high in RA patients (17,18) and others (19,20) showed that adiponectin was high in SLE than control. On the other hand, Barbosa et al (21) , concluded that the level of adiponectin was not high in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Serum adiponectin was high in both SLE and RA patients in comparison to control (P <0.001). Many studies showed that adiponectin was high in RA patients (17,18) and others (19,20) showed that adiponectin was high in SLE than control. On the other hand, Barbosa et al (21) , concluded that the level of adiponectin was not high in SLE patients.…”
Section: Discussionmentioning
confidence: 99%